Doktor hab. Zbigniew Oniszczuk, profesor Uniwersytetu Śląskiego (1955-2020). In Memoriam… - Wielopolska-Szymura, Mirosława; Grzonka, Bernard (Studia Politicae Universitatis Silesiensis, 2020)
Wspomnienie o prof. UŚ, dr.hab. Zbigniewie Oniszczuku (1955-2020)